Nanocomposite films consisting of functional nanoparticles (TiO2 and ZnO) embedded in 4A-Zeolite and mixed polymer matrices (gelatin and polyvinyl alcohol). (November 2020) - Azizi-Lalabadi, Maryam; Alizadeh-Sani, Mahmood; Divband, Baharak; Ehsani, Ali; McClements, David Julian
Graphical abstract: Highlights: PVA and gelatin matrices were used as carriers for active colloidal nanoparticles. TiO2 and ZnO nanoparticles exhibited effective antimicrobial activity in the films. Zeolite was used as a support for the nanoparticles to control their release from films. These biocompatible nanocomposites are suitable as new active packaging materials. Abstract: In this study, nanocomposite films with enhanced functional properties were prepared by loading titanium dioxide (TiO2 ) and/or zinc oxide (ZnO) nanoparticles within 4A zeolite (4AZ) particles, and then incorporating these nanocomposites into a poly (vinyl alcohol) (PVA) and gelatin matrix. The composition and morphology of the films were characterized using atomic force microscopy (AFM), scanning electron microscopy (SEM), Fourier transform infrared (FTIR), and X-ray diffraction (XRD). The thermal behavior of the films was established using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). SEM showed the nanoparticles were dispersed throughout the films when used at these levels. FTIR indicated that the inorganic nanoparticles interacted with the PVA/gelatin polymer network through hydrogen bonding. XRD confirmed that the nanoparticles were in a crystalline state within the films. DSC and TGA showed that introduction of the nanoparticles modified the nanocomposite's thermal behavior. Nanoparticle addition had a number of effects: (i) it decreased film transparency from 78.7% to 69.4% 72.0% and 69.7%; (ii) it decreased film water vapor permeability (WVP) from 8.20 × 10 −9 to 5.13 × 10 −9, 5.71 × 10 −9 and 5.24 × 10 −9 g/Pa.h.m; (iii) it reduced film oxygen permeability from 4.57 to 3.29, 3.10 and 3.00 mEq/g; and (i) it increased film tensile strength (TS) from 14.6 to 22.0, 20.3 and 18.0 MPa, for PVA/gelatin films containing 0%, 1.5% ZnO, 1.5% TiO2 and 1% (ZnO + TiO2 ) nanoparticles, respectively (with the nanoparticles being trapped within 4AZ). Moreover, active nanocomposite films exhibited significant antimicrobial effects especially against gram-negative bacteria. Overall, our results show that nanoparticle-loaded PVA/gelatin nanocomposites may be useful as active biodegradable nanocomposite films for application in the packaging industry and that their properties can be modulated by controlling the nature and level of nanoparticles incorporated.